Genomic Signatures for Avian H7N9 Viruses Adapting to Humans - Chen, Guang-Wu (PLoS One, 2016)
An avian influenza A H7N9 virus emerged in March 2013 and caused a remarkable number of human fatalities. Genome variability in these viruses may provide insights into host adaptability. We scanned over 140 genomes of the H7N9 viruses isolated from humans and identified 104 positions that exhibited seven or more amino acid substitutions. Approximately half of these substitutions were identified in the influenza ribonucleoprotein (RNP) complex. Although PB2 627K of the avian virus promotes replication in humans, 45 of the 147 investigated PB2 sequences retained the E signature at this position, which is an avian characteristic. We discovered 10 PB2 substitutions that covaried with K627E. An RNP activity assay showed that Q591K, D701N, and M535L restored the polymerase activity in human cells when 627K transformed to an avian-like E. Genomic analysis of the human-isolated avian influenza virus is crucial in assessing genome variability, because relationships between position-specific variations can be observed and explored. In this study, we observed alternative positions that can potentially compensate for PB2 627K, a well-known marker for cross-species infection. An RNP assay suggested Q591K, D701N, and M535L as potential markers for an H7N9 virus capable of infecting humans.